Systematic review of Tulostoma (Agaricomycetes: Agaricales) from MEXU National Fungarium: new records and new species - Hernández-Navarro, Eduardo; Agustín-López, Carlos San (Phytotaxa, 2025)
A taxonomic and phylogenetic study of Tulostoma specimens deposited in the MEXU Fungal Collection of the National Herbarium is presented. Eleven collections were morphologically characterized with light microscopy (LM) and Scanning Electron Microscopy (SEM). DNA was extracted with a CTAB 3% protocol. The nrITS (ITS1-5.8S-ITS2), nrLSU (28S), and partial tef1-α were amplified and sequenced from both directions. The phylogenetic analysis consisted of Maximum Likelihood and Bayesian Inference Analysis of the ITS+28S, and a concatenated matrix of ITS+28S+tef1-α. Both analyses recovered 11 clades. T. exasperatum, T. rufum, and T. simulans are confirmed species in the Mexican Funga. T. obscurum materials correspond with T. punctatum, a new record for Mexico. Three new species are described: T. elvirae, T. evangelinae, and T. teophili. Photographs of specimens and micrographs of light and electron scanning microscopy are provided. Comparison with related taxa is discussed. With the new additions, 56 species are currently known in Mexico.